Polish travellers on the move: A study of knowledge of travel health and associated practices among polish travellers abroad - Anna Bogacka; Agnieszka Wroczyńska; Maciej Grzybek (Travel Medicine and Infectious Disease)
Background: Post-pandemic travel has surged, with 1.3 billion journeys recorded worldwide in 2023, reflecting a growing interest in tropical destinations despite the associated health risks. Access to travel health information has improved, yet adherence to preventive measures remains limited due to misinformation, insufficient pre-travel consultations, and concerns about malaria prophylaxis. Based on data from a three-year survey, this study examines the attitudes of Polish travellers to vaccinations, malaria prophylaxis, and COVID-19-related measures. Methods: Surveys conducted during travel festivals from 2021 to 2023 targeted adult participants. A questionnaire designed by experts in travel medicine addressed the demographics, travel behaviours, and health-related practices. Statistical analyses, including chi-squared tests and logistic regression, explored the impact of demographic factors on behaviours, using Python for data analysis. Results: Among 644 participants (mean age 32; 48 % male), 49.5 % reported pre-travel vaccination and 281 intended to use malaria chemoprophylaxis. Gender significantly influenced vaccination status and travel to Africa. The most cited malaria prevention methods were repellents and mosquito nets. Illnesses were reported by 317 participants, with travellers' diarrhoea (185 cases) most common, particularly in Turkey, Egypt, and India. Forty-eight individuals required medical consultations. Conclusions: Education and pre-travel counseling enhance adherence to preventive measures, yet many travellers fail to follow recommendations. Malaria remains the most common travel-imported disease in the EU/EEA, with 4856 cases in 2021. The Capability, Opportunity, and Motivation Behavior (COM-B) model highlights the importance of addressing these factors to improve compliance with preventive behaviours.